2022
DOI: 10.7554/elife.79405
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of liver diurnal transcriptome rhythms by triiodothyronine (T3) supplementation

Abstract: Diurnal (i.e., 24-hour) physiological rhythms depend on transcriptional programs controlled by a set of circadian clock genes/proteins. Systemic factors like humoral and neuronal signals, oscillations in body temperature, and food intake align physiological circadian rhythms with external time. Thyroid hormones (THs) are major regulators of circadian clock target processes such as energy metabolism, but little is known about how fluctuations in TH levels affect the circadian coordination of tissue physiology. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 49 publications
4
35
0
Order By: Relevance
“…For mesor and amplitude comparison, CircaCompare was allowed to fit a sine curve irrespective of rhythmicity thresholds. Phase comparison was only performed in robustly rhythmic genes as described (2).…”
Section: Supplemental Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For mesor and amplitude comparison, CircaCompare was allowed to fit a sine curve irrespective of rhythmicity thresholds. Phase comparison was only performed in robustly rhythmic genes as described (2).…”
Section: Supplemental Materials and Methodsmentioning
confidence: 99%
“…1a; Table S1). Considering the marked rhythmicity of the liver transcriptome and liver metabolism (11,33) one explanation for this lack of consistency would be differences in sampling times and control thereof between studies.…”
Section: Nashmentioning
confidence: 99%
“…As one example, we recently showed that alterations in thyroid hormone state leads to a rewiring of the circadian liver transcriptome in mice. 14 Besides transcriptional control, clock proteins have been shown to interact with many other proteins. 15 These post-transcriptional hands provide further levels of complexity to the circadian regulation of physiology.…”
Section: Circadian Network Organizationmentioning
confidence: 99%
“…8,9 Circadian profiling of mouse livers showed that 10% or more of the transcriptome is rhythmically expressed. 14,21 It should be mentioned that the percentage of rhythmic genes varies widely between different studies depending on several factors such as sequencing method, temporal sample resolution, and algorithms to assess rhythmicity. The concordance between rhythmic genes and proteins is not linear and often both rhythms are not overlapping, suggesting that post-transcriptional and -translational modifications are important players in the generation of physiological rhythms.…”
Section: Meets the Clock…mentioning
confidence: 99%
See 1 more Smart Citation